Regulatory Requirements Of Combinational Products: An Overview (Usfda) - Shah, Binal (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTA regulation with respect to combination products and FDA over view, advances in drug, biologic and medical device development relate to both single entities and combination of each type of medicinal product. Regulatory overview of combination products is complicated by the fact that although drugs are regulated primarily under food, drugs and cosmetic act and reviewed by CDER, CBER, and CDRH. Combination products increasingly include state-of-art, innovative technologies with great potential to advance patient care. Combining different regulated product types, however, triggers a panoply of issues with which the Food and Drug Administration, pharmaceutical, biologic and medical device manufacturers, and other stake holders have struggled through the years. Since 1991, FDA has worked toward resolving a number of these issues, and has made some inroads in assignment of jurisdiction for combination products. We are encouraged by FDA?óÔé¼Ôäós preliminary efforts, and look forward to further improvement in the regulatory process for combination products.